The Reality of Knowledge Management in Islamic Higher Education - Munadi, Muhammad; Ernawati, Fetty; Hakiman (Jurnal Pendidikan Islam, 2018)
Knowledge Management (KM) is an approach to understand how the known processes are created, used, and shared to enhance academic productivity. This study aims to determine the system of implementation of KM in Islamic higher education, having the work unit status of non-tax state revenue (Penerimaan Negara Bukan Pajak/PNBP) and public service agency (Badan Layanan Umum/BLU) and applying remuneration. This study utilizes a qualitative method with the phenomenological approach. Data collection take through observation, in-depth interviews, document analysis, and focus group discussions. The implementation of KM is with the result of academic knowledge from research products and research schemes of educational staffs, saving knowledge storage on the database through electronic and printed forms, and the knowledge taking a distribution on through printed and electronic forms which are referencing lecture notes and oral sources such as scientific consortium and lecturing. The successful implementation of KM requires support by stakeholder policies in educational institutions. The research findings present an overview of the implementation design of KM that can be used as a platform by scholars and stakeholders in educational institutions to increase knowledge productivity.